2021
DOI: 10.7759/cureus.18419
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Natural Formulation Containing Activated Charcoal, Calcium Sennosides, Peppermint Oil, Fennel Oil, Rhubarb Extract, and Purified Sulfur (Nucarb®) in Relieving Constipation

Abstract: IntroductionLong-term use of laxatives may have side effects such as bloating, allergic reaction, abdominal pain, metabolic disturbances, and hepatotoxicity. In this study, we have compared the efficacy of herbal medicine Nucarb, a combination of activated charcoal, calcium sennosides, peppermint oil, fennel oil, rhubarb extract, and purified sulfur, in relieving constipation. MethodsThis longitudinal study was conducted in multiple cities of Pakistan from April 2021 to June 2021. A total of 1000 patients, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Vitamin C has abundant biological activities, but its laxative properties have not been reported. Through a systematic literature review, we found that the presence of sodium, potassium, calcium, magnesium and phosphorus in nature in various forms have different degrees of relief for constipation, including calcium sennosides, magnesium oxide, magnesium sulfate, sodium hyaluronate, and potassium binder ( Dupont et al, 2019 ; Ali et al, 2021 ; Mori et al, 2021 ; Imamura and Kinugawa, 2022 ; Vacca et al, 2022 ). In particular, dietary magnesium and phosphorus are closely related to the occurrence of constipation ( Zhang et al, 2021 ; Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C has abundant biological activities, but its laxative properties have not been reported. Through a systematic literature review, we found that the presence of sodium, potassium, calcium, magnesium and phosphorus in nature in various forms have different degrees of relief for constipation, including calcium sennosides, magnesium oxide, magnesium sulfate, sodium hyaluronate, and potassium binder ( Dupont et al, 2019 ; Ali et al, 2021 ; Mori et al, 2021 ; Imamura and Kinugawa, 2022 ; Vacca et al, 2022 ). In particular, dietary magnesium and phosphorus are closely related to the occurrence of constipation ( Zhang et al, 2021 ; Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%